Transformative listening across global contexts: Fostering authentic connection to self, other and community - Laurie Anderson Sathe; Tes Cotter Zakrzewski; Alessandra Romano; Anne-Liisa Longmore; Deborah J. Kramlich (Adult Education Research Conference, 2021)
As a group of global scholars, we see authentic listening, with its focus on attention and presence, as crucial to the formation of trust, connection, and the facilitation of learning. We co-created the Transformative Listening Collaborative and a Transformative Listening Protocol (the Protocol) as a means to increase awareness of the importance of authentic listening as a transformative component of learning through story. The Protocol is intended to improve listening skills, foster deep sense-making, and generate contextually situated spaces in which participants may connect with another, understand another, and/or learn more deeply about oneself.
Keywords: listening; protocol; transformation; global; connection